2008
DOI: 10.1111/j.1444-2906.2007.01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence effect on survival and feeding of Pacific bluefin tuna Thunnus orientalis larvae, on the basis of a rearing experiment

Abstract: Physical conditions such as oceanic turbulence related to food availability are considered to be important factors affecting fish larval survival. Rearing experiments were conducted to elucidate the effects of turbulence on the survival and feeding rates during the initial feeding period of Pacific bluefin tuna Thunnus orientalis. Six levels of turbulence intensity were provided by changing flow rates from pipes set on the bottom of rearing tanks. The result showed a dome-shaped relationship between turbulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…For the improvement of egg and larval quality, future work needs to consider improved broodstock diets that may improve egg quality and fecundity (Watanabe and Vassallo‐Agius, 2003). The availability of certain turbulence levels in the larval rearing tanks, which have shown improvements in feeding and survival rates of yellowfin tuna ( Thunnus albacares ) (Kimura et al., 2004) and Pacific bluefin tuna (Kato et al., 2008) should also be implemented in ABFT in order to achieve a better success in larval rearing. Once the ABFT begin feeding, more work should be done on the type of feeds that are fed to the larvae.…”
Section: Resultsmentioning
confidence: 99%
“…For the improvement of egg and larval quality, future work needs to consider improved broodstock diets that may improve egg quality and fecundity (Watanabe and Vassallo‐Agius, 2003). The availability of certain turbulence levels in the larval rearing tanks, which have shown improvements in feeding and survival rates of yellowfin tuna ( Thunnus albacares ) (Kimura et al., 2004) and Pacific bluefin tuna (Kato et al., 2008) should also be implemented in ABFT in order to achieve a better success in larval rearing. Once the ABFT begin feeding, more work should be done on the type of feeds that are fed to the larvae.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to specify mechanisms inducing converse effects of the egg size and the mixing of rearing water on the growth rate of PBT larvae. Kato et al () reported that a strong water current (turbulence) induced a low feeding incidence. However, it is reported that PBT larvae are daytime feeders (Uotani et al ), and in the present study, we conducted the mixing of rearing water by strong aeration during the night.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, it was found that manipulating the aeration levels to vertically mix the rearing water reduced the number of larvae sinking to the tank bottom. This may be the case in PBT larviculture, also, as water flow significantly affects the survival and feeding of PBT larvae (Kato et al, 2008).…”
Section: Rearing In the Early Larval Stagementioning
confidence: 99%